Osteoporosis in Inflammatory Arthritides: New Perspective on Pathogenesis and Treatment - Rotta, Denise; Fassio, Angelo; Rossini, Maurizio; Giollo, Alessandro; Viapiana, Ombretta; Orsolini, Giovanni; Bertoldo, Eugenia; Gatti, Davide; Adami, Giovanni (Frontiers in Medicine, 2020)
Osteoporosis is a skeletal disorder characterized by impaired bone strength and increased risk of fragility fracture and is among the most relevant comorbidities of rheumatic diseases. The purpose of the present review is to discuss the pathogenesis of local and systemic bone involvement in inflammatory arthritides, especially Rheumatoid Arthritis, Psoriatic Arthritis, and Spondyloarthritides, as well as the effect of anti-rheumatic treatments and anti-osteoporotic medication on bone health and fracture incidence, including recent data on novel therapeutic perspective.